Peran Guru PAI dalam Mencegah Perilaku Bullying di SMP Muhammadiyah 1 Probolinggo - Huda, Mufti Miftahul; Khadavi, M Jadid (Pendidikan Agama Islam STIT Palapa Nusantara, 2025)
This study aims to examine the role of Islamic Education (PAI) teachers in preventing bullying behavior at SMP Muhammadiyah 1 Probolinggo. Bullying is a serious issue that can negatively impact students' mental health and social development. Therefore, it is important to explore strategies that can be applied to prevent such behavior in the school environment. The method used in this study is descriptive qualitative, with data collected through in-depth interviews, participatory observation, and document analysis. The research subjects include the Principal, Vice Principal, PAI teachers, students, and other relevant parties. The results show that PAI teachers play an important role in integrating Islamic values, such as tolerance, compassion, and mutual respect, into daily learning. Through the teaching of the Qur'an and Hadith, which are relevant to social issues, students are taught the importance of positive social interactions. Additionally, various extracurricular activities provide students with opportunities to engage in positive activities, thus reducing bullying behavior. Collaboration between PAI teachers, school staff, and parents has proven effective in creating a safe and supportive learning environment. This study concludes that a proactive, religion-based approach can be an effective solution in preventing bullying in schools.